Perancangan UI/UX Website Promosi Kos-Kosan Menggunakan Pendekatan Design Thinking - Nadya Satya Handayani; Kawan Pandiangan; Muhammad Farhan Basri; Novia Ernawati Sitohang; Desi Mulia Putri; M Syafiq Naufal; Alrifan Rahardyan Ihsan (Politeknik Negeri Batam, 2026)
The increasing use of digital technology has transformed promotional strategies, including in the boarding house industry. High population mobility in Batam City has created a growing demand for accessible and informative boarding house promotions. This study aims to design an interactive website as a promotional medium for boarding houses. A descriptive quantitative method was employed through questionnaires to identify user needs and preferences. The findings were used to guide the design process using the Design Thinking approach, which includes empathize, define, ideate, prototype, and test stages. The resulting website provides information on prices, facilities, locations, photos, and videos, enabling prospective tenants to obtain more comprehensive and up-to-date information. The website also offers a simple and integrated interface for both tenants and boarding house owners. The developed platform is expected to enhance promotional effectiveness and support users in finding suitable accommodation.